The Determinant of Internal Control Effectiveness on Cooperative Employees of the Republic of Indonesia in Semarang City - Rizki, Putra; Anisykurlillah, Indah (Universitas Negeri Semarang, 2018)
This research aims to obtain empirical evidence the influence of competence, motivation, role and work experience on the effectiveness of internal control cooperatives in Semarang either partially and simultaneously. The population in this research are 132 Koperasi Pegawai Republik Indonesia (KPRI) in Semarang in 2017. The sampling technique used is simple random sampling and used sample size with non-statistic technique. With this technique gained as much as 31 sample research of Koperasi Pegawai Republik Indonesia. Collecting data uses questionnaires. While the analysis method used is multiple regression analysis with the analysis tool is SPSS Statistic 23.The results showed that competence and motivation partially have a positive and significant effect on the effectiveness of internal control cooperative. Role and work experience partially failed to show any significant effect on the effectiveness of internal control. While the results of competence, motivation, role and work experience simultaneously have a positive and significant impact on the effectiveness of internal control. The conclusion of the research are obtained evidence that competence and motivation have a positive and significant effect on the effectiveness of internal control. Meanwhile, role and work experience does not have effect on the effectiveness of internal control.